Anti-EPLIN antibody development - Remes, Sylvia (My University, 2023)
Head and neck cancers are the seventh most prevalent cancers worldwide with the predominant subtype head and neck squamous cell carcinomas (HNSCC) accounting for over 90 % of these cases. Late diagnosis and start of treatment, insufficient prognosis, and high mortality rates due to lack of biomarkers and screening methods for HNSCCs have presented an issue in treatment of the patients. Epithelial protein lost in neoplasm (EPLIN) is a cytoskeletal actin binding protein expressed as two isoforms, EPLIN-α and EPLIN-β. According to still unpublished studies, EPLIN-α protein has been linked with aggressive clinical behaviour of HNSCC. Currently, there are commercial antibodies detecting total EPLIN, however no available binders are capable of specifically recognizing just either one of the isoforms. The objective of this MSc’ thesis project was to develop an antibody for the detection of EPLIN-β isoform. The project was carried out by generating a rediversified antibody binding fragment (Fab) library by shuffling variable heavy (VH) domains of previously enriched single chain fragment variable (scFv) binders and variable light (VL) domains of a universal phage display library. The Fab binders were then enriched by phage display method in three rounds of panning against a peptide of EPLIN-β followed by screening for high-affinity binders with immunoassays as well as sequencing of positive clones. Additionally, seven clones were characterized by half maximal effective concentration (EC50) determination. Sequencing of the seven Fab clones showed each of them having a unique VL chain whereas for VH three different sequences were found. The most common VH chain appeared in four clones showing good binding capabilities with EC50 values of 10.5 – 13.7 nM. All Fab binders had improved affinity compared to the scFv binders that had been previously enriched towards the same target peptide through two rounds of phage display. According to AlphaFold structure and binding predictions, all the best four Fab binders bind the target peptide at amino terminus similarly except one Fab binder with slightly altered binding orientation. After conversion to intact immunoglobulin G (IgG), these binders can be used in immunohistochemistry application for prognosis of HNSCC.
Keywords: head and neck squamous cell carcinoma, HNSCC, phage display, antibody, epithelial protein lost in neoplasm, EPLIN